PENYULUHAN KASUS KEHAMILAN YANG TIDAK DIKEHENDAKI PADA TENAGA KESEHATAN - R Sri Rezeki; Sri Legawati; Efi Irwansyah Pane; Ade Febriani Nst; Azwar Rifky Sinaga; Putri Ramadhani (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Unintended pregnancy (KTD) is a serious problem in the world of reproductive health, including among health workers. This study aims to identify factors that contribute to the occurrence of KTD in health workers at RSU Ibu Kartini Kisaran in February 2023. This study used a quantitative descriptive design with a cross-sectional approach. Data were collected through a questionnaire from 30 respondents who experienced KTD. The results showed that most health workers who experienced KTD were 20–30 years old, unmarried, and had limited knowledge about contraception. The main causal factors were lack of access to contraception, partner pressure, and social stigma against the use of contraception among health workers. These results indicate the need for educational interventions and internal hospital policies that support the reproductive health of health workers. This study is expected to be the basis for developing health promotion programs and reproductive counseling in the hospital environment.